The influence of concrete strengths on the behaviour of external beam-column joints [electronic resource] - 239856 Idayani Salim (Skudai : Universiti Teknologi Malaysia, 2007)
Thesis (Sarjana Kejuruteraan (Awam - Struktur)) - Universiti Teknologi Malaysia, 2007